PD-1/PD-L1 inhibitors plus chemotherapy versus chemotherapy alone for Asian patients with advanced triple-negative breast cancer: a phase III RCTs based meta-analysis - Ruan, Hua; Zou, Yubin; Huang, Lifeng; Zha, Wenjuan; Ouyang, Qingqing; Yang, Ling (Frontiers in Oncology, 2025)
BackgroundAdvanced triple-negative breast cancer (TNBC) presents significant therapeutic challenges, particularly in Asian populations, which exhibit distinct biological and genetic characteristics. Immunotherapy combined with chemotherapy has emerged as a promising approach; however, its efficacy compared to chemotherapy alone remains under investigation. This meta-analysis aims to evaluate the clinical outcomes of PD-1/PD-L1 inhibitors combined with chemotherapy (PIC) versus chemotherapy alone in the treatment of advanced TNBC in Asian patients.MethodsA systematic literature search was performed across six databases for phase 3 randomized controlled trials (RCTs). Only studies comparing the outcomes of PIC versus chemotherapy alone in patients with advanced TNBC, including subgroup analyses of Asian populations, were included. Data were pooled to assess overall survival (OS), progression-free survival (PFS), responses, and safety profiles.ResultsA total of 1041 patients from five phase 3 RCTs were included in the final analysis. Compared to chemotherapy alone, PIC therapy significantly improved PFS (hazard ratio [HR]: 0.74 [0.62, 0.88], P = 0.0008). No significant difference was observed in OS (HR: 0.78 [0.55, 1.12], P = 0.18), although a slight trend favoring PIC therapy was noted. Among PD-L1-positive patients, both OS (HR: 0.62 [0.44, 0.86], P = 0.005) and PFS (HR: 0.66 [0.50, 0.86], P = 0.003) were significantly improved in the PIC group. The PIC group also exhibited a substantially higher OS rate at 12–36 months and a higher PFS rate at 6–30 months. However, the incidence of immune-related AEs (irAEs) (risk ratio [RR]: 1.69 [1.33, 2.15], P < 0.0001) and grade 3–5 irAEs (RR: 3.11 [1.59, 6.10], P = 0.001) was significantly higher in the PIC group. The most common irAEs in the PIC group were hypothyroidism (14.40%), dermatitis (10.00%), and infusion reactions (8.85%). Both treatment groups exhibited similar response rates and treatment-related AEs (TRAEs).ConclusionsIn Asian patients with advanced TNBC, PIC significantly improved survival compared to chemotherapy alone. Although the combination therapy was associated with a higher incidence of irAEs, its clinical benefits support its use as a viable treatment option for this population.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024622428.